Spinoza contra Curie - Richey, Lance Byron (Philosophy & theology, 1993)
I outline Spinoza’s development of the concept of conatus in the Ethics, and attempt to define its role in his metaphysics. In light of this, I critique the theory based on the identification by modern physics of certain radioactive substances, e.g., curium. These substances, I argue, are by definition unstable individuals whose essences include finite durations (half-lives). As such, they are in direct contradiction to Spinoza’s metaphysics. I then advance and critique several defenses Spinoza might make for his theory of conatus.